The serotonin receptor 5-HT2A modulates lifespan and protein feeding in Drosophila melanogaster - Munneke, Allyson S.; Chakraborty, Tuhin S.; Porter, Saige S.; Gendron, Christi M.; Pletcher, Scott D. (Frontiers in Aging, 2022)
The conserved neurotransmitter serotonin has been shown to be an important modulator of lifespan in specific nutritional contexts; however, it remained unclear how serotonin signaling influences lifespan under normal conditions. Here, we show that serotonin signaling through the 5-HT2A receptor influences lifespan, behavior, and physiology in Drosophila. Loss of the 5-HT2A receptor extends lifespan and induces a resistance to changes in dietary protein that are normally detrimental to lifespan. 5-HT2A-/- null mutant flies also display decreased protein feeding and protein content in the body. Therefore, serotonin signaling through receptor 5-HT2A is likely recruited to promote motivation for protein intake, and chronic reduction of protein-drive through loss of 5-HT2A signaling leads to a lower protein set-point adaptation, which influences physiology, decreases feeding, and increases lifespan. Our findings reveal insights into the mechanisms by which organisms physiologically adapt in response to perceived inability to satisfy demand.